A tracer to bridge the scales: on the value of diatoms for tracing fast flow path connectivity from headwaters to meso‐scale catchments. Issue 25 (2nd September 2015) - Klaus, Julian; Wetzel, Carlos E.; Martínez‐Carreras, Núria; Ector, Luc; Pfister, Laurent
Abstract: Connectivity between different landscape units and flow paths to the stream has gained much attention in hydrological science. Recent work has focused on the threshold sequencing of spatial sources in upland forested watersheds, connectivity and its spatial patterns in the hillslope–riparian–stream continuum. Fast flow path connectivity in the HRS continuum is still difficult to decipher because of the scale‐limitations of hydrometric and tracer methods. Such connectivity may be strongly non‐linear and controls streamflow response and chemistry. Recently, diatoms, one of the most common and diverse algal groups, were used to detect the onset and cessation of surface runoff to small headwater streams and constrain hydrograph separation methods. In this work, we investigate the potential for diatoms to determine fast flow path connectivity between their habitat and the stream over various scaled catchments. We used seven nested sub‐catchments (0.45 to 247 km 2 ) with uniform and mixed geologies and land use types within the Attert River catchment (Luxembourg) for testing our hypothesis. We categorized the prevailing diatom communities based on their habitat in the hillslope–riparian–stream continuum of one headwater catchment and sampled a storm event for diatom communities in every catchment. We present the diatom dynamics during the event hydrograph. We also outline different occurring species of diatoms and present that combinations of species or individual species can be used as a tracer for source area connectivity. Further, we show that the occurrence of aerial diatom species decreases by a power law with scale, potentially limiting the scale of application. Finally, we discuss how diatoms could indicate temporal variability of contributions from different physiographic units. Copyright © 2015 John Wiley & Sons, Ltd.